O religijskom pravu u sekularnim državama / On religious law in secular states: ima li mjesta za Šerijat? / is there space for Sharia? - Karčić, Harun (Context: Journal of Interdisciplinary Studies, 2022)
Michael J. Broyde, Shari’a Tribunals, Rabbinical Courts, and Chris-tian Panels: Religious Arbitration in America and the West, Oxford University Press, 2017. Str. 312, ISBN 978 0 19064 028 6. The Problem of Religious Diversity: European Challenges, Asian Approaches, By Anna Triandafyllidou & Tariq Modood (eds.), Edinburgh: Edinburgh University Press, 2017. Str. 352, ISBN 978 1 47441 909 3.